Producing the Bestiary: From Text to Image - Dines, Ilya (2020)
In this paper, I investigate the relationship between the text and the images in medieval Latin bestiary manuscripts. Medieval bestiaries, which are derived from the ancient Physiologus, comprise a nearly 1800-year-old tradition and have spawned several hundreds of copies throughout Europe, including a smaller subset of Latin bestiaries. Summarizing the first ever comprehensive analysis of the entire corpus of Latin bestiaries, this paper examines the patterns of deviations, or exceptions from the rigorous canon governing bestiary illustrations. I use the deviations to investigate the relationship between the work of the scribe and that of the artist in the production of bestiary manuscripts in order to determine to what extent medieval artists used already existing illustrations, and, conversely, when and to what extent they were willing or able to deviate from the canon. In the latter case, I try to explore the artist’s possible motivations, as well as the reasons for choosing specific motifs.   Bibliography BRODEUR, Arthur G. – “The Grateful Lion”. Publications of the Modern Language Association of America 39 (1924), pp. 485-524. BROWN, Arthur C. – “The Knight of the Lion”. Publications of the Modern Language Association of America 20 (1905), pp. 673-706. CLARK, Willene B. – A Medieval Book of Beasts: The Second-Family Bestiary. Commentary, Art, Text and Translation, Woodbridge: Boydell, 2006. CURLEY, Michael – Physiologus: A Medieval Book of Nature Lore. Chicago and London: Univ. of Chicago Press, 1979. DINES, llya – “The Hare and its Alter Ego in the Middle Ages”. Reinardus: Yearbook of the International Reynard Society 17 (2004), pp. 73–84. DINES, Ilya – “The Problem of the Transitional Family of Bestiaries”. Reinardus: Yearbook of the International Reynard Society (2013), pp. 29-52.